Regulatory Effect of Tibolone on Antiinflamatory Activity of Macrophage - Aguayo-Cerón, K. A.; Morales-González, J. A.; Iglesias-Gutiérrez, G.; Parra-Barrera, A.; Jiménez-Zamarripa, C. A.; Ocharán-Hernández, M. E.; Calzada-Mendoza, C. C. (Revista Mexicana de Ingenieria Biomedica, 2019)
Macrophages are phagocytic cells that activate NOS and NADPH oxidase to eliminate agents that recognize like strangers, also participate in development and maintain of inflammatory response. In other hand, tibolone (Tb) has three main metabolites, which have an estrogenic, progestogen and androgenic activity. This drug is a hormonal therapy to treat symptoms of menopause, with ability to decrease inflammation markers. The aim of this study is to describe the effect of Tb on macrophage activity. This study was carried out on differentiated macrophage THP-1 cell line used. NADPH oxidase activity by NBT assay and expression of IL-1β, IL-6, TNF-α and IL-10 by RT-qPCR were measured. It has been observed that Tb regulates the enzymatic activity, as well as the cytokines expression in the cells that received a proinflammatory stimulus; these results contribute to description of mechanism of action of this drug. The results suggest that macrophage could be a target for anti-inflammatory action of Tb. Its remain to investigate the protein expression of cytokines and activity of iNOS.